Development Model of Brick Business Competitiveness: Study on Brick Business Groups in Limbung District, Bajeng District, Gowa District - Anwar (PT. Maju Malaqbi Makkarana, 2024)
This research departs from the fact that MSMEs are the pillars of economic growth to date, but their business growth is hampered by problems of weak control of strategic resources and limited market access. The general aim of this research is to examine the development of a brick business competitiveness model. The research method uses a quantitative approach with an emphasis on explanatory research. The sample units are brick businesses located in Limbung Village, Bajeng District, Gowa Regency, totaling 65 businesses. Data collection used a survey with a questionnaire instrument using a Likert scale measurement. Respondents are asked to provide answers to closed statements. The respondents are brick business owners. The data analysis method in this research uses descriptive statistics to describe research variables and inferential statistics through PLS (Partial Least Square) analysis version of the WarpPLS 4.0 program. The results of the research analysis will be supported and deepened using a qualitative approach through in-depth interviews with several key informants and stakeholders.